Perbahasan Halia (zanjabil) Berdasarkan Al-quran, Hadis Dan Manuskrip Perubatan Melayu - Robiatul Adawiyah Mohd @ Amat; Norzulaili Mohd Ghazali; Adnan Mohamed Yusoff; Muhammad Widus Sempo (Perpustakaan Negara Malaysia, 2024)
Non-Indexed Publication